Nada-Nada Persatuan: Manifestation of the Third Principle of Pancasila in the Meugang Through Experimental Music - Rico Gusmanto; Dwindy Putri Cufara; Rika Wirandi (Gondang: Jurnal Seni dan Budaya, 2025)
Meugang is a tradition of the Acehnese people that is carried out before Ramadan, Eid al-Fitr, and Eid al-Adha, and is rich in values of togetherness and mutual cooperation. These values are in line with the third principle of Pancasila, namely “Indonesian Unity”. Previous studies have focused on meugang as a cultural and social tradition but have not explored its ideological dimension nor its potential as the conceptual basis for musical experimentation. This research fills that gap by applying a practice-led artistic research approach, integrating observation, and interviews with Meugang practitioners. This music inspired by Cage’s sound philosophy and Lachenmann’s concept of musique concrete instrumentale. the result is an experimental music titled  Nada-Nada Persatuan (Tones of Unity), structured around three core values of mutual cooperation namely unity, harmony, and balance. The study finds that music can function as both aesthetic construction and an ideological metaphor, enabling local cultural practices to articulate national identity through sound. This research contributes to the discourse on Indonesian experimental music by demonstrating how cultural-ideological concepts can be systematically translated into sonic structures.